Exploring factors hampering the performance of business incubators in South Africa – a public, private, and university business incubator cross-case analysis - Matthee, Sabrina Vinette (Stellenbosch : Stellenbosch University, 2023)
Thesis (MCom)--Stellenbosch University, 2023.